Sexual and reproductive health and access: Results of a rapid epidemiological assessment among migrant peoples in transit through Darién, Panamá - Erausquin, Jennifer Toller; Sánchez, Joanne; Yu Pon, Anyi; Jhangimal, Mónica; Millender, Eugenia; Peña, Yudith; Ng, Winroy; Reina, Adelys; Nakad, Candy; Quintana, Joselid; Herrera Veces, Roberto; Vistica, Grace; et al. (Frontiers in Reproductive Health, 2022)
Background The foot transit of migrant peoples originating from the Caribbean, South America, Asia, and Sub-Saharan Africa through the Darién Forest (DF) in Eastern Panamá towards North America has increased in recent years from approximately 30,000 people/year to >133,000 in 2021. In the DF, there is no food/housing provision nor healthcare access. Very little is known of sexual and reproductive health (SRH) among this population. This study used rapid epidemiological methods to describe the SRH situation among migrant peoples in transit through the DF. Methods This cross-sectional study randomly selected migrant people in transit (men and women) at a Migrant Reception Station in Darién, Panamá, between January 4–11, 2022. Data collection included a self-applied questionnaire (≥18 years); clinical screening (≥12 years); and HCG, treponemal antibodies, and HIV(I/II) lateral-flow tests with blood samples (≥12 years). Descriptive analyses were used to report findings. Results In all, 69 men and 55 women participated in the self-applied questionnaire, 70 men and 51 women in clinical screening; 78 men and 63 women in HCG, treponemal antibody and HIV testing. Overall, 26.1% (18/69) men and 36.4% (20/55) women reported sexual intercourse within the past month. The last sex partner was casual among 43.0% (21/49) of men and 27.8% (10/36) of women; of those, 42.9% (9/21) of men and 80.0% (8/10) of women reported this sex was condomless. Among women, 20.0% (11/55) tested positive for pregnancy; 5 of these pregnancies were planned. Of those screened, a reproductive tract infection symptom was reported by 5.7% (4/70) of men and 58.8% (30/51) of women. A total of 32.7% (18/55) of men and 18.2% (8/44) of women reported no prior HIV testing. Of 78 men, HIV and treponemal antibodies were found among 1.3% (n = 1) and 2.6% (n = 2), and among 63 women, 3.2% (n = 2) and 3.2% (n = 2), respectively. Conclusions This rapid epidemiological assessment found high recent sexual activity, low condom use with casual partners, and a need for increased HIV and syphilis testing and treatment. There is a need for increased testing, condom provision, and SRH healthcare access at migrant reception stations that receive migrant peoples in transit through Panamá.